An Analysis of Advertisement, Customer's Purchasing Performance and Behaviors: A Case Study on Kurdistan Region ‎ - Hamze, Murad (Humanities Journal of University of Zakho, 2020)
Advertisement is usually used for making promoting and consciousness of products. It plays a vital role in changing and attracting the attitude and behaviour of customers. The aim of this study was to explore the impact of advertisement on customer's purchasing performance and behaviour in Kurdistan. For this purpose, the quantitative approach was used through questionnaire-based survey from 107 participants who were randomly selected in Kurdistan. The collected data were analyzed through SPSS and Microsoft Excel. The results revealed that, among personal, economic, cultural, social and psychological factors, personal factors have the most substantial impact on consumer's purchasing performance and behavior, which is about 40 (37.4%), while, psychological ones have the least effect on them, which is about 11 (10.3%). For further study, the qualitative method through interviews has been proposed. Keywords: Impact, Advertisement, Factors, Customer, Buying, Purchasing behaviour